Merger Class Actions in Delaware and the Symptoms of Multi-Jurisdictional Litigation - Adam B. Badawi (Washington University Law Review, 2013)
Recent research on corporate litigation has focused on three trends: the growth in percentage of mergers that result in litigation, the migration of cases away from Delaware, and the increasing prevalence of merger litigation occurring simultaneously in multiple jurisdictions. This Article uses a new and unique dataset of public company litigation to track how these trends have affected filings and litigation tactics in the Delaware Court of Chancery from 2004 to 2011. The data confirm that Delaware appears to have experienced a decline in filings during the early and middle periods of the sample, but the data also shows that there has been a sharp increase in the number of the number of acqusition-related cases filed in Delaware in 2010 and 2011. The rise of concurrent, multi-jurisdictional litigation and the litigation tactics that it encourages are the likely reasons for the growth of acquisition-related cases in Delaware. While some plaintiffs’ attorneys may have left Delaware to escape the Chancery’s threats of lower attorneys’ fees and merit-based selection of lead counsel, in the current environment a Delaware filing may provide strategic advantages as foreign jurisdictions become saturated with filings. For example, lawyers may try to take control of a case by moving for expedited proceedings in Delaware or they may try to complicate negotations over the selection of lead plaintiffs’ counsel. The threat of using these tactics may increase the possibility that a plaintiff will receive some share of a fee award either in Delaware or in a case being litigated elsewhere. This Article explores how the rules Delaware uses to manage deal cases may enable strategic behavior in the context of multi-jurisdictional litigation. This discussion provides reasons to believe that the use of tactics such as requesting expedited proceedings, contesting consolidation of cases, and involving out-of-state counsel earlier in proceedings should increase as multi-jurisdictional litigation increases. The empirical evidence provides substantial support for these theories. The Article concludes with an assessment of how the observed increase in strategic tactics may affect debates over how and whether to respond to the rise of multi-jurisdictional litigation.
Keywords: corporate litigation; corporate; multi-jurisdictional; Delaware Court of Chancery; merger; acquisition